The Local Wisdom of Batak Toba through the Philosophy of Dalihan Na Tolu in a Kinship Environment - Rufer Firma Harianja; Ajat Sudrajat (BIRCU, 2021)
Local wisdom is a wisdom of noble values that is still wise and relies on a philosophy of behavior and ethics. Batak Toba has a wisdom that regulates the system and life patterns of others, known as Dalihan Na Tolu. This paper discusses how the Dalihan Na Tolu philosophy affects the kinship system in the Batak Toba community and its benefits for the wider community. To interpret the data, this paper uses a qualitative method with a content analysis approach to analyze in depth what is in a discussion in the text, which can be grouped according to the theme or material to be studied. Dalihan Na Tolu is connected from the old belief of the Batak Toba tribe to Mula Jadi Na Bolon (God of the universe) who also rules the three realms, namely the heavens, the earth and after death. Dalihan Na Tolu has a philosophy, namely somba marhula-hula, manat mardongan tubu, and elek marboru”. It means that every Batak person must respect / obey his wife's family, be careful with family members and be obedient to his husband's side. The cultural system of dalih na tolu is required to behave helping or caring for relatives at every opportunity and this behavior for the Toba Batak people is perceived as a high value and is also a noble and noble act. In fact, the Dalihan Natolu philosophy is not only for the Batak people, because fair, social and religious values are the needs of every human being.